THE ROLE OF MICROBIAL COMMUNITIES IN ECOSYSTEM FUNCTIONING: A ZOOLOGICAL AND ECOLOGICAL APPROACH - Aylin Erdogan; Baran Akbulut; Serdar Zeynalov (Yayasan Adra Karima Hubbi, 2025)
The microbial communities play a crucial role in maintaining ecosystem functions by driving various biological processes, including nutrient cycling, energy flow, and species interactions. Despite extensive studies on individual species, the holistic role of microbial communities within ecosystems, particularly from a zoological and ecological perspective, remains underexplored. This study aims to analyze the interrelationship between microbial communities and ecosystem functions, emphasizing their impact on animal health, productivity, and biodiversity. The research employs a combination of field observations, laboratory analyses, and statistical modeling to investigate microbial diversity across different habitats. Field samples were collected from diverse ecosystems, including forests, grasslands, and aquatic environments, to assess microbial composition and its association with local fauna. Results indicate significant correlations between microbial diversity and ecosystem productivity, with specific microbial taxa contributing to enhanced nutrient availability and animal health. Moreover, the findings reveal that changes in microbial communities due to environmental stressors, such as climate change and habitat fragmentation, can negatively affect ecosystem resilience. In conclusion, this study highlights the pivotal role of microbial communities in supporting ecosystem functions, providing a basis for conservation strategies that integrate microbial management to enhance ecological balance and sustainability.